GENERALIZATION AND RESOLUTION OF THE HOMOGENEOUS REACTION-DIFFUSION EQUATIONS BY THE METHOD OF FACTORIZATION OF ORDINARY DIFFERENTIAL OPERATORS - MASSOU, SIAKA; MOUMOUNI, Sounmaila; SOUMANOU, Serge; ESSOUN, ADÉBAYO LOUIS; TCHOFFO, Martin (My University, 2016)
The objective of this article is the generalization of the homogeneous reaction-diffusion equations of the monostable or bistable types. From the non-linear second order differential equation of the front profile (solution of the homogeneous reaction-diffusion equations), a method of generalization of the homogeneous reaction-diffusion equations, based on the theory of factorization of ordinary differential operators [9], was proposed. This method enables us to build two generalized homogeneous reaction-diffusion equations: the first with one species and the second with two species.
Keywords: homogeneous reaction-diffusion equations; method of factorization of; ordinary differential operators; population dynamics.